DOES ORGANIZATIONAL CULTURE AND SERVANT LEADERSHIP IMPROVE HEALTH WORKERS' ENGAGEMENT IN HOSPITALS? - Miawati, Tita; Junengsih, Junengsih; Yosminaldi, Yosminaldi (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
Numerous research studies have recently found that hospital health worker engagement correlates directly with critical safety, quality, and patient experience outcomes. Therefore, it is important to understand the current States of health worker engagement and its drivers to provide reliable services to patients. This study aims to determine the effect of organizational culture and servant leadership on health worker engagement in hospitals. The study participants consisted of 193 front-line health workers who had taken random sampling techniques from health workers of three hospitals. The study used a survey method designed by questionnaires. The research found that organizational culture has a positive and significant effect on health worker engagement in hospitals. Otherwise, servant leadership has a positive but not significant effect on health worker engagement in hospitals. The findings of this study recommend creating a structured, transparent, involving everyone in the process to some degree and progressive organizational culture in hospital.